2021
DOI: 10.1101/2021.01.22.21250321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors influencing nursing students’ intention to accept COVID-19 vaccination – A pooled analysis of seven countries

Abstract: Experiencing the second wave of COVID-19 pandemic, high vaccination coverage by a safe and effective vaccine globally would be a great achievement. Acceptance of vaccination by healthcare students is an important issue as they have a key role as future professionals in educating patients, informing and guiding them to the right clinical decision. The aim of this study was to explore the intention of nursing students to get vaccinated for SARS-CoV-2 infection and the factors acting either as motivators or barri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 46 publications
(62 reference statements)
5
19
3
2
Order By: Relevance
“…Malik et al (2020) found that participants who had more trust in medicine got information from healthcare workers and health officials, whereas those who collected sources from social media had less trust in medical science. Similar results were found by Patelarou et al (2021), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020;Obiała et al, 2020;Patelarou et al, 2021).…”
Section: Role Of Trust In Information Sources In Vaccination Behaviorsupporting
confidence: 73%
See 4 more Smart Citations
“…Malik et al (2020) found that participants who had more trust in medicine got information from healthcare workers and health officials, whereas those who collected sources from social media had less trust in medical science. Similar results were found by Patelarou et al (2021), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020;Obiała et al, 2020;Patelarou et al, 2021).…”
Section: Role Of Trust In Information Sources In Vaccination Behaviorsupporting
confidence: 73%
“…Similar results were found by Patelarou et al (2021), showing that those who got information from newspapers, television, radio, and government agencies had more trust in the COVID-19 vaccine than those who had self-perceived knowledge or collected information through social or online media. In fact, misinformation is more available on the internet where the information may be less accurate or verified (Liu and Yang, 2020;Obiała et al, 2020;Patelarou et al, 2021). Skeptics also use online platforms to advocate vaccine refusal.…”
Section: Role Of Trust In Information Sources In Vaccination Behaviorsupporting
confidence: 73%
See 3 more Smart Citations